The Legacy of Professor Dmitry Zernov: Anatomist, Scientist and Educator - Sinelnikov, Mikhail; Nikolenko, Vladimir; Rizaeva, Negoriya; Shumak, Anna; Oganesyan, Marine; Prozhirov, Timur; Bulygin, Kirill; Chairkin, Ivan (Medicina Historica, 2022)
Dimitry Nikolayevich Zernov (1843-1917) was a renowned Russian anatomist, emeritus professor, head of the medical faculty and president of Moscow Imperial University, and a prominent international collaborator. One of his most important contributions to medicine was as active advocation of international outreach of an otherwise isolated medical scientific society. Seeking to understand advanced technologies being used in Germany, Dr. Zernov completed an internship with the famous German professors Salmon Stricker and Ernst Brucke. To promote Russian science, he published his articles in international journals. Occupying the post of head of the medical faculty, Zernov sought to improve the quality of education based on his personal research into best practices developed by visiting a number of foreign institutions and observing innovative approaches to teaching medical disciplines. He always shared his experiences and knowledge with students and colleagues. Zernov was a pioneer in exploring of structure of the brain and invented the encephalometer, a unique device for anatomical studies, the ancestor of modern stereotaxic apparatus. Among his seminal contributions were ‘Individual Types of Brain Convolutions in Humans’, ‘On the limits of individual and tribal modifications of typical grooves and convolutions of the brain’, ‘On the anatomical features of the brain of intelligent people’ as well as refuting a controversial theory advanced by Italian psychiatrist Lombroso about innate predisposition to commission of crimes. Zernov’s legacy lives on today in the heart of anatomists and surgeons, as well as the Russian anatomical medical community.